Postgraduate events as a building block for interdisciplinary research. Issue 4 (10th September 2015) - Darlington, Eleanor; Waite, Catherine; Balsdon, Stacey
Abstract : Postgraduate students are at the forefront of geographical research, forging their career in a rapidly changing landscape. The ideology of geography as a single discipline is being erased, enabling complex geographical questions spanning both natural and social sciences to be properly addressed. A postgraduate event organised in a thematic manner, rather than by discipline, reveals that postgraduate students still associate with 'human' or 'physical' geography, rather than with interdisciplinary work. However, students who overcome time constraints and have exposure to, or engage with, interdisciplinary research gain valuable transferable skills, enhancing research outputs and employability. Therefore, postgraduate perceptions of interdisciplinary research are important for geography to advance.